A coaxial probe fed wideband circularly polarized antenna using unequal and adjacent‐slided rectangular dielectric resonators for WLAN applications. Issue 4 (28th November 2017) - Chowdhury, Rakesh; Kumar, Rajkishor; Chaudhary, Raghvendra Kumar
Abstract: In this article, a coaxial probe fed wideband circularly polarized antenna has been designed and investigated using unequal and adjacent‐slided rectangular dielectric resonators radiating in broadside direction (Φ = 0°, θ = 0°). Wi‐Fi wireless network use radio signal either in 2.4 or 5 GHz band. Owing to high rush in 2.4 GHz band, the proposed antenna is designed for 5 GHz (5.15‐5.825 GHz) WLAN band. The proposed design uses fundamental orthogonal modes TE δ 11 X and TE 1 δ 1 Y excited in two individual rectangular dielectric resonators to achieve wide axial‐ratio bandwidth (below 3 dB). Measured input reflection coefficient (below −10 dB) and axial ratio bandwidth (below 3 dB) of 26.07% (5.27‐6.85 GHz) and 26.85% (5.32‐6.97 GHz) has been attained, respectively, in this proposed antenna. The measured far‐field patterns such as gain and radiation patterns are showing consistent performance throughout the working band.